2018
DOI: 10.3390/su10072293
|View full text |Cite
|
Sign up to set email alerts
|

Size of Membership and Survival Patterns of Producers’ Organizations in Agriculture—Social Aspects Based on Evidence from Poland

Abstract: Agricultural producer organizations are considered to be an efficient way for farmers to build up bargaining power, thereby increasing farmers' incomes. While making a contribution to the research on the longevity of cooperatives, we tried to identify some regularities concerning the survival of these entities in the specific context of transition economies. In this paper, we look more closely at potential relationships between the development of producers' organizations (POs) and the size of their membership.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Cooperation in POs may be justified by the advantages of the economies of scale and the willingness to minimize transaction costs accompanying the processes of producing and selling dairy products. Furthermore, it is worthwhile mentioning that a side effect of the producer groups' existence might be the links between producers, processors and commercial agents; these links could be important for the efficient functioning of the market, resulting in market and price stabilization [57]. Like other European Union countries, Poland has also provided support from public funds for the setup and operation of producers' organizations.…”
Section: Determinants Of Changes In Spatial Integration On the Milk Mmentioning
confidence: 99%
“…Cooperation in POs may be justified by the advantages of the economies of scale and the willingness to minimize transaction costs accompanying the processes of producing and selling dairy products. Furthermore, it is worthwhile mentioning that a side effect of the producer groups' existence might be the links between producers, processors and commercial agents; these links could be important for the efficient functioning of the market, resulting in market and price stabilization [57]. Like other European Union countries, Poland has also provided support from public funds for the setup and operation of producers' organizations.…”
Section: Determinants Of Changes In Spatial Integration On the Milk Mmentioning
confidence: 99%
“…Chlebika and Pietrzak study the potential relationship between the survival of Polish producer organizations and farmers' social capital [5]. They focus on two research questions: (1) does the size of membership matter for the survival of producer organizations?…”
Section: Emerging Themes and Insights From The Special Issuementioning
confidence: 99%
“…Most studies on agricultural producers' cooperation, however, concentrate on how small or family farms can benefit from membership in APOs and factors of APO survival, e.g. EC (2019b); Chlebicka and Pietrzak (2018). Giagnocavo et al (2018) showed that companies with a cooperative structure for marketing, financing, processing and other collective services, are an effective organizational coordination mechanism for small-scale farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Country studies analyzing APOs in the EU look at the functioning, size, role, and factors of the establishment of APOs. For instance, Banaszak and Beckmann, (2010), Matczak (2012), and Chlebicka and Pietrzak (2018) analyzed the functioning and establishment of APOs in Poland and reached diverse conclusions. Ratinger et al (2012) found that APOs of dairy farms in the Czech Republic were relatively successful in gaining higher bargaining power.…”
Section: Literature Reviewmentioning
confidence: 99%